Value Approach and Character Education in Reviewing Cohabitation Phenomenon - Ni Luh Gede Yogi Arthani (Sociological Jurisprudence Journal, 2019)
Coexistence between two people who have a love affair without marriage ties is called cohabitation, or what is in Indonesian language termed "kumpul kebo." This cohabitation phenomenon is not only found in urban areas, but also in rural areas. Some people in Indonesia reject this behavior because it is considered contrary to the cultural values, while the others let the people around them take the decision to live together. The refusal by local community members was carried out by persecuting lovers who allegedly committed cohabitation. This certainly makes other legal problems. In this study, two issues will be discussed namely cohabitation behavior which is categorized as a criminal act and an attempt to criminalize cohabitation in the legal system in Indonesia. Not all cohabitation behaviors are categorized as criminal acts. Cohabitation as a criminal offense is if it is carried out by people who are already married to another person as stipulated in Article 284 of the Criminal Code. The efforts to criminalize cohabitation in the legal system in Indonesia are carried out by submitting applications in the Constitutional Court and cohabitation arrangements in the Draft of Penal Code.